Needs and prospects for crime-fighting technology : the federal role in assisting state and local law enforcement - Schwabe, William, 1942-; Science and Technology Policy Institute (Rand Corporation); Rand Corporation; United States. Office of Science and Technology Policy (Santa Monica, CA : RAND, 1999)
Most policing in the United States is done by law enforcement agencies at the local level. Although most Americans prefer that policing be controlled locally, there is considerable support for federal help in funding police. One area in which federal funding has been seen as useful is in the development, testing, and implementation of improved technology. An initiative proposed by the Clinton administration would increase funding of state and local law enforcement, with emphasis on technology assistance, technology deployment, crime lab improvements, and training. This report provides information on the current status in each of these, gives examples of what has been accomplished, and suggests prospects for improvements.
"Science and Technology Policy Institute."
Includes bibliographical references (p. 67-70).
Also available on the internet via WWW in PDF format.
Keywords: Crime prevention -- United States; Criminal justice, Administration of -- United States; Federal aid to law enforcement agencies -- United States; Law enforcement -- Technological innovations -- United States; Law enforcement -- United States -- Equipment and supplies